Bioremediation characteristics, influencing factors of dichlorodiphenyltrichloroethane (DDT) removal by using non-indigenous Paracoccus sp. (May 2021) - Al-Rashed, Sarah; Marraiki, Najat; Syed, Asad; Elgorban, Abdallah M.; Prasad, Kollur Shiva; Shivamallu, Chandan; Bahkali, Ali H.
Abstract: The marine bacterium able to consume DDT as the nutrient source was isolated from sea water which was identified as Paracoccus sp. DDT-21 based on 16 S rDNA gene sequence and Gram negative rod, obligate aerobic, non-motile biochemical characteristics. The isolate can degrade over 80% of the DDT, at a concentration of 50 mg/L in MSM in 72 h. Time and pollutant (DDT) dependent growth studies indicated that the isolate Paracoccus sp., DDT-21 significantly degrade the DDT and tolerates under DDT stress up to 50 mg/L. The DDT degradation capability of the strain Paracoccus sp. DDT-21 was found to be 5 ˃ 10 ˃ 15 ˃ 25 ˃ 50 mg/L DDT. The high concentrations (75 and 100 mg/L) of DDT showed significant decrease in DDT degradation. The optimal DDT degradation (∼90.0%) was observed at 6 g/L of yeast extract, 6% of glucose in pH 7.0 at 35 °C with 72 h of incubation as constant. Furthermore, four metabolites were observed by GC-MS analysis such as, DDE, DDD, DDMU, and DDA. The obtained results indicate that the isolate Paracoccus sp. DDT-21 is a promising candidate for the removal and/or detoxification of DDT in the environment. Highlights: The isolate Paracoccus sp. DDT-21 could degrade over 80% of the 50 mg/L DDT within 72 hrs. The optimum DDT degradation (∼90.0%) was observed at 6 g/L of yeast extract, 6% of glucose in pH 7.0. DDE, DDD, DDMU, and DDA metabolites were observed by GC-MS analysis.